Developing of prototype of e-saman: case study Bahagian Keselamatan UiTM / Rosdy Oto - Oto, Rosdy (Faculty of Information Technology and Quantitative Sciences, 2005)
Electronic System is a systemi of integrated programs designed to make it easier for a user to discover information in a convenient way and become a vital to our life rather then Manual System. For these proposed, the development of e- Saman for Security Department of UiTM is being build up to detemnine the staff acceptance level of the e-Saman system and also to develop a solution replacing the existing conventional system with a web-based computerized system. A questionnaire is been produced as the instruments to assemble the data and 100 respondents from Security Department staffs were chosen to observe their acceptance on the implementation of the e- Saman in their department. The systems were developed using PHP, which is a programming language. In addition MySQL, and Apache server are used in developing this system. MySQL will acts as the database where all the data regarding the system will be stored in MySQL and Apache Server determination as server in this system. During developing the process. System Development Life Cycle (SDLC) was implemented where it operate as a methodology in raising the system. The outcome of this study will recommend and put fonward to convert from manual system to e-Saman at Security Department of UiTM.